O centro público e seu papel na política de economia solidária: um estudo de caso do processo de implantação do Centro Público Estadual de Economia Solidária - Eco Paraíba - Rodrigues, Rodrigo Moreira (2024)
This dissertation aims to analyze the implementation process of the Public State Center for Solidarity Economy of Paraíba and its role in the implementation of public policy in the State. Solidarity economy is an innovative economic approach that seeks to promote a more collaborative and fair approach in the economic sphere, based on cooperation, solidarity, and centered on the pursuit of human fulfillment. The research takes as theoretical and conceptual reference the foundations and practices of the solidarity economy, conceptualized by Paul Singer as a creation of workers in struggle against capitalism, an economic and politicalideological option that goes against the dominant values of individual competition and the supremacy of capital over labor. In this sense, the solidarity economy represents a set of alternative experiences of work and income generation, which emerged as a response to the economic crisis of the 80s and aim to overcome wealth concentration, social exclusion, ecosystem destruction, and human exploitation. These experiences are supported by public policies that aim to strengthen these practices and the experimentation of programs, projects, actions, and equipment that correspond to the principles and values of the solidarity economy. The research was based on a case study and can be classified as qualitative, descriptive, and explanatory. The analysis sought relational and causal elements that sought to describe in the implementation process of the Public Center the insertion and the role played by this equipment in the implementation of public policy in the State. The analysis allowed us to understand its position in the State Policy, but also to identify the structuring role played, considering the management model adopted and the interaction with the various agents involved.